Current-pressure-position triple-loop feedback control of electro-hydrostatic actuators for humanoid robots. (17th December 2018) - Ko, Tianyi; Kaminaga, Hiroshi; Nakamura, Yoshihiko
ABSTRACT: To overcome the tradeoff between torque density and response of the backdrivable actuators, actuation by electro-hydrostatic actuators (EHA) is effective. While their backdrivability and energy efficiency was shown in the previous studies, their closed-loop dynamic behavior was not discussed in detail. In this paper, we present the analysis and experimental evaluation of the force control performance of the electro-hydrostatic actuator for the humanoid robot 'Hydra'. We first present a simplified model of EHA and show that EHA can be simplified as a mass-spring-damper model if all values such as pump torque/velocity and fluid pressure/flow-rate are expressed in the equivalent value seen from the actuator. We also show the comparison between the model and experimentally acquired open-loop dynamic behavior. Then, the evaluation on the force measurement and control performance is shown. The static friction on the rod-seal was 0.46% of the maximum piston force, and with additional strain gauge information, the error can be reduced to 0.28% of the maximum force. We also show that our developed EHA has a pressure control bandwidth of 100 Hz in the fixed piston configuration, which is higher than other state-of-the-art series elastic actuators. In the last of paper, the joint level position and torque control performance of Hydra is examined. GRAPHICAL ABSTRACT: